2019
DOI: 10.1111/head.13568
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety Sensitivity as a Risk Indicator for Anxiety, Depression, and Headache Severity in Women With Migraine

Abstract: Objective The primary aim of this exploratory study was to assess the relationship between anxiety sensitivity and emotional disorders, migraine characteristics, and migraine‐related fear and avoidance behaviors in women with probable migraine. Background Anxiety and depressive disorders are the most frequent comorbid psychiatric conditions in migraine, particularly in women; however, the underlying reasons for these comorbidities are uncertain. Anxiety sensitivity, the tendency to catastrophically appraise an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…The present study showed that migraine sufferers have a range of moderate to severe pain-related anxiety, according to the PASS score (47.4 ± 17.2). It is known that anxiety is significantly associated with an increased risk of migraine 30,38 . The PCS is a tool for evaluating catastrophizing chronic pain disorders.…”
Section: Discussionmentioning
confidence: 99%
“…The present study showed that migraine sufferers have a range of moderate to severe pain-related anxiety, according to the PASS score (47.4 ± 17.2). It is known that anxiety is significantly associated with an increased risk of migraine 30,38 . The PCS is a tool for evaluating catastrophizing chronic pain disorders.…”
Section: Discussionmentioning
confidence: 99%
“…Because migraine has a strong association with depression and anxiety, clinicians and patients often gravitate toward the incorrect conclusion that one disease “causes” the other 39. These conditions should be considered comorbidities and treated as such, as treating one condition can often favorably affect the other 4041. Patients should be screened for stress and mood disorders and referred appropriately for treatments as needed.…”
Section: Treatment Of Chronic Migrainementioning
confidence: 99%
“…Although there are no studies showing that sleep reactivity and anxiety sensitivity are associated with specific physical diseases, anxiety sensitivity has been found to be associated with pain severity in headaches [ 29 ].…”
Section: Introductionmentioning
confidence: 99%